Fiber Composite Splint in Tooth Mobility accompanied by Esthetic Correction of Microdontia and Tooth Rotation: Case Report: Fiber composite splint pada mobilitas gigi disertai koreksi estetika mikrodonsia dan rotasi gigi - Dwis Syahriel Dwis Syahriel; Asri Riany Putri; Dwis Syahrul; Arya Kusuma Agraha (Makassar Dental Journal, 2023)
Teeth 12, 11, 21, 22 had degree 2-mobility. Tooth 22 had rotation, and anatomically small or microdontia, and diastema 21-22. There was slight inflammation on the upper anterior gingiva and the patient felt discomfort when chewing. Scaling, root planing and periodontal flap surgery were performed about 1 month ago. Anatomical shape and rotation on 22, and diastema on 21-22 were corrected with direct composite laminate veneer technique. Splints on teeth 13, 12, 11, 21, 22, 23 functioned well. Tooth 22 as well as diastema 21-22 were well corrected. It is concluded that composite fiber splints effectively correct maxillary anterior tooth mobility while correcting the anatomical shape of microdontia and rotational teeth.